2012
DOI: 10.1007/s13644-011-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Donations, and Disadvantage: The Implications of Personal Fundraising for Racial Diversity in Evangelical Outreach Ministries

Abstract: Employing insights from critical whiteness theory, I analyze the fundraising experiences of racial minorities within predominantly white evangelical outreach ministries (EOMs) in order to assess the ways in which the funding structure of EOMs contributes to the reproduction of white structural and cultural dominance and, ultimately, racial homogeneity within these organizations. Quantitative and qualitative data from a mixed-race sample of EOM workers (N = 716) reveal that white dominance is reproduced within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
(43 reference statements)
2
18
1
Order By: Relevance
“…The multivariate analyses above indicated that minority respondents, and African Americans and Latinos in particular, experience greater difficulty raising financial support than their white counterparts, but that this difficulty was due in large part to social capital deficits (see Table). Interestingly, although previous studies have reported that Asian‐American EOM workers experience greater fundraising challenges relative to whites (Morton ; Perry ; Sommer ), these differences were not evidenced in the multivariate findings. This is likely because Asian Americans tend to come from higher SES families and communities relative to blacks and Latinos, and they also tend to be more familiar with evangelical parachurch (particularly collegiate) organizations (Garces‐Foley ; Kim ).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The multivariate analyses above indicated that minority respondents, and African Americans and Latinos in particular, experience greater difficulty raising financial support than their white counterparts, but that this difficulty was due in large part to social capital deficits (see Table). Interestingly, although previous studies have reported that Asian‐American EOM workers experience greater fundraising challenges relative to whites (Morton ; Perry ; Sommer ), these differences were not evidenced in the multivariate findings. This is likely because Asian Americans tend to come from higher SES families and communities relative to blacks and Latinos, and they also tend to be more familiar with evangelical parachurch (particularly collegiate) organizations (Garces‐Foley ; Kim ).…”
Section: Resultscontrasting
confidence: 61%
“…Moreover, Asian Americans have evidenced a pattern of ethnic‐specific giving and will likely fund other Asian Americans (Shao ). Consequently, the greater challenges that Asian‐American fundraisers face relative to whites are likely less attributable to instrumental social capital deficits and more due to differing cultural norms regarding the solicitation of financial donations (direct, business‐like solicitations vs. showing deference to elders) and what constitutes an appropriate livelihood for college‐educated individuals (Morton ; Perry , ; Sommer )…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, studies of “evangelical outreach ministries” (i.e., parachurch organizations) have found that African Americans attempting to raise funds for such ministries tend to face cultural obstacles within their congregations, as African‐American congregations emphasize donating to social justice causes or congregationally organized outreach activities, not outreach directed by external actors (Carson ; Perry , ; Pressley ). As Perry states (:411), African‐American fundraisers reported that “‘parachurch ministries’ in general…were largely unfamiliar to their families, social networks, and their…ethno‐religious tradition.” Such evidence would seem to support an expectation that the presence of African‐American Protestantism in a community would weaken parachurch foundings.…”
Section: Environmental Conditions Supporting Parachurch Foundingsmentioning
confidence: 99%
“…This is consistent with a large body of literature on racial diversity in religious communities (Emerson & Woo, 2006). Ethnic minorities bear disproportionate personal costs in mixed congregations, being less integrated (Christerson & Emerson, 2003); having less access to leadership positions (Perry, 2012;Rosette, Leonardelli, & Phillips, 2008); and, eventually, having a greater likelihood of leaving the community (Scheitle & Dougherty, 2010). Even though demographic attributes such as race are not directly tied to the theological beliefs of most congregations (i.e., they are surface-level traits), being different from others in terms of race, age, and social status will nevertheless influence one's ability to form close relationships within the community.…”
Section: Meaghermentioning
confidence: 99%
“…The naturally occurring racial segregation of religious communities within the United States reflects the general inability of diverse religious communities to have its members transcend ethnic groupings (Marti, 2010). Moreover, structural issues regarding existing social injustices frequently prevents members of minority groups from gaining positions of leadership in the church, thereby hindering the potential amelioration of such conflicts (Perry, 2012). As a result, group-level diversity appears capable of causing internal conflict.…”
mentioning
confidence: 99%